Ovarian Hyperstimulation syndrome combined with hypothyroidism: a comprehensive review - Jing Zhou; Yu Chen; Lijing Bai; Wei Zhou; Haiyan Yang; Yang Chen; Li Chen; Renjie Lu; Lingmin Hu; Shuxian Wang (BMC, 2024)
Abstract Ovarian Hyperstimulation Syndrome (OHSS) is a systemic condition marked by the enlargement of the ovaries and heightened vascular permeability. And hypothyroidism (HT) emerges as a potential risk factor for OHSS occurrence. This review presented a comprehensive summary of pertinent case reports involving patients diagnosed with both HT and OHSS. Detailed exploration was conducted into their clinical presentations, diagnostic methodologies, and treatment modalities. Additionally, the review delved into potential interaction mechanisms between HT and OHSS, encompassing various aspects including hormone levels. Moreover, management strategies for mitigating the risk of OHSS in HT patients were thoroughly reviewed and the importance of monitoring thyroid function in those experiencing OHSS was emphasized. This review indicated that the association between HT and OHSS, underscoring its multifaceted complexity. It could accentuate the ongoing necessity for rigorous research and clinical refinement to deepen our comprehension of this association and to bolster diagnostic and therapeutic methodologies for optimal patient care. In conclusion, this review offered valuable insights for future research directions and clinical practices for patients afflicted with OHSS and HT.